2010
DOI: 10.1038/ijo.2010.245
|View full text |Cite
|
Sign up to set email alerts
|

Obesity predicts persistence of pain in children with functional gastrointestinal disorders

Abstract: Objective: The possible effect of obesity in the outcome of treated children with abdominal pain-related functional gastrointestinal disorders (FGIDs) has not yet been studied. We hypothesized that obesity is associated with a poor long-term prognosis in children with FGIDs. Study design: Prospective cohort study in an outpatient clinic-based sample of patients diagnosed with abdominal pain-related FGIDs. Principal outcome measured was persistence of pain at long-term follow-up (12-15 months). Frequency of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 29 publications
1
30
1
1
Order By: Relevance
“…Known factors influencing persistence of symptoms: patients who struggle to effectively employ coping strategies;42hospitalisation due to pain or reports of very high pain scores;27non-GI symptoms;26obese children (p<0.0017, over 12–15 months follow-up) 43…”
Section: ‘Is There Anything Else We Can Do To Help?’mentioning
confidence: 99%
“…Known factors influencing persistence of symptoms: patients who struggle to effectively employ coping strategies;42hospitalisation due to pain or reports of very high pain scores;27non-GI symptoms;26obese children (p<0.0017, over 12–15 months follow-up) 43…”
Section: ‘Is There Anything Else We Can Do To Help?’mentioning
confidence: 99%
“…Obesity has also been associated with poor outcome and disability at long-term follow-up of standard medical treatment for these symptoms (16). Obese children are more likely to report higher intensity and frequency of symptoms, school absenteeism, and lower levels of daily functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested a higher prevalence of FGIDs (including functional abdominal pain) in obese and overweight children (13, 14), and data have shown relationships between obesity and AP in children with FGIDs (16), however, these studies did not include an evaluation of QOL. Studies that do investigate QOL in children and adolescents with AP have shown global impairments (48, 50), although BMI/weight status was not known in those populations.…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition to above mentioned life threatening problems, several investigators have noted FGIDs are significantly more common in children with obesity. In a prospective study of children with FGIDs, Bonilla et al 4 found obese patients complain more pain intensity, higher pain frequency, more school absenteeism and more disruption of daily activities. Another study assessed children referred to a paediatric gastroenterology clinic and compared them with local population.…”
Section: Commentmentioning
confidence: 99%